2022
DOI: 10.1039/d1qi01045j
|View full text |Cite
|
Sign up to set email alerts
|

La(iii)–curcumin-functionalized gold nanocomposite as a red light-activatable mitochondria-targeting PDT agent

Abstract: Red light-activable transition metal complexes have recently emerged as the viable alternative for photodynamic/photochemotherapeutic applications. Ideal photosensitizers or photochemotherapeutic agents are still an elusive goal. Here in, we have reported...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Recently, a chemotherapeutic curcumin-acetazolamide-dimethylnitrothiophene compound was reported by Sessler et al, which inhibits the proliferation of CSCs of MDA-MB-231 (triple-negative breast cancer) in the dark. 56 The stable 3,4difluorobenzylidene curcumin (CDF) used by Sessler et al is also found to be active against colon cancer stem cells by Majumdar et al 57 Earlier curcumin-based PDT agents 53,[58][59][60][61][62][63][64] (Fig. 1) have been shown to participate in type-I or type-II photo processes displaying antiproliferative activity against a wide range of cancer cells, and suitable functionalization has led to organelle targeting capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a chemotherapeutic curcumin-acetazolamide-dimethylnitrothiophene compound was reported by Sessler et al, which inhibits the proliferation of CSCs of MDA-MB-231 (triple-negative breast cancer) in the dark. 56 The stable 3,4difluorobenzylidene curcumin (CDF) used by Sessler et al is also found to be active against colon cancer stem cells by Majumdar et al 57 Earlier curcumin-based PDT agents 53,[58][59][60][61][62][63][64] (Fig. 1) have been shown to participate in type-I or type-II photo processes displaying antiproliferative activity against a wide range of cancer cells, and suitable functionalization has led to organelle targeting capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Photo-aquation of both the ligand is shown in the complex [Cr(NH 3 ) 5 Br] 2 + , [Cr(NH 3 ) 5 Cl] 2 + . [36,145] The substitution pathway of chromium complexes follows two rules known as Adamson's rules which states that: A. The ligand which lies in the axes of least average field strength is labile and the incoming ligand will approximate the total quantum yield of the octahedral complex.…”
Section: Photo-substitution Reactionmentioning
confidence: 99%
“…Excited states of a molecule have different electronic distribution and geometries undergoing isotropic or anisotropic distortions, bond angle, bond length and have higher rotational and vibrational energy than the ground state. [36][37] In the excited state, the metal-ligand bond length of complexes can be elongated selectively allowing the facile exchange of ligands. The excited state is often a stronger reductant and oxidant than the ground state of a molecule.…”
Section: Electronic Transitions and Photoactivated States Of Transiti...mentioning
confidence: 99%
See 1 more Smart Citation
“…S5 and S6 †). [52][53][54] The folic acid and complex co-functionalized gold nanoparticles (Fe@FA-AuNPs) were prepared by the subsequent addition of a methanolic solution of the complex (0.7 × 10 −3 M, 20 mL) and an aqueous solution of FA-en-LA (0.7 × 10 −3 M, 20 mL) with constant stirring overnight under ambient conditions. A colour change from wine-red of gold nanoparticles (AuNPs) to a dark blue solution indicated the formation of a nanohybrid (Fe@FA-AuNPs).…”
Section: Synthesis Characterisation and General Aspectsmentioning
confidence: 99%